Finance and development - Sen, Sunanda; Dutt, R.C. (Calcutta Orient Longman Limited, 1998)
R.C. Dutt Lectures on Political Economy, 1994.
Lecture one Lecture two
Includes appendix and notes.
Keywords: ECONOMICS; CENTRE FOR STUDIES IN SOCIAL SIENCES, CALCUTTA